Interspecific Plant Interactions Reflected in Soil Bacterial Community Structure and Nitrogen Cycling in Primary Succession - Knelman, Joseph E.; Graham, Emily B.; Prevéy, Janet S.; Robeson, Michael S.; Kelly, Patrick; Hood, Eran; Schmidt, Steve K. (Frontiers in Microbiology, 2018)
Past research demonstrating the importance plant-microbe interactions as drivers of ecosystem succession has focused on how plants condition soil microbial communities, impacting subsequent plant performance and plant community assembly. These studies, however, largely treat microbial communities as a black box. In this study we sought to examine how emblematic shifts from early-successional Alnus sinuata (alder) to late successional Picea sitchensis (spruce) in primary succession may be reflected in specific belowground changes in bacterial community structure and nitrogen cycling related to the interaction of these two plants. We examined early successional alder-conditioned soils in a glacial forefield to delineate how alders alter the soil microbial community with increasing dominance. Further, we assessed the impact of late-successional spruce plants on these early-successional alder-conditioned microbiomes and related nitrogen cycling through a leachate addition microcosm experiment. In total, we show how increasingly abundant alder select for particular bacterial taxa. Additionally, we found that spruce leachate significantly alters the composition of these microbial communities in large part by driving declines in taxa that are enriched by alder, including bacterial symbionts. We found these effects to be spruce-specific, beyond a general leachate effect. Our work also demonstrates a unique influence of spruce on ammonium availability. Such insights bolster theory relating the importance of plant-microbe interactions with late-successional plants and interspecific plant interactions more generally.